Penyuluhan Hukum Tentang Lalu Lintas Di Kelurahan Palabusa Kota Bau-Bau - Rizki Mustika Suhartono; Wa Ode Al Zarliani; Indah Kusuma Dewi; Ernawati Ernawati; Ni Ketut Diyan Cahyanti (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
This community service aims to provide knowledge and understanding of the orderly traffic of the Palabusa Village community. This community service is expected to provide legal awareness to the community about the importance of obeying traffic for safety. The method used to implement the activity is counseling and asking and answering. The results and discussion, Community Service, is legal counseling involving Amaliah Work Lecture (KKA) students to provide legal counseling in front of the Palabusa Village community. Legal education on traffic is very much needed for all ages, considering that there are still many drivers, both teenagers, and adults, who do not obey traffic rules